2016
DOI: 10.1111/ejn.13259
|View full text |Cite
|
Sign up to set email alerts
|

Role of cAMP signalling in winner and loser effects in crayfish agonistic encounters

Abstract: For territorial animals, establishment of status-dependent dominance order is essential to maintain social stability. In agonistic encounters of the crayfish Procambarus clarkii, a difference of body length of 3-7% is enough for larger animals to become dominant. Despite a physical disadvantage, small winners of the first pairings were more likely to win subsequent conflicts with larger inexperienced animals. In contrast, the losers of the first pairings rarely won subsequent conflicts with smaller naive anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 77 publications
(101 reference statements)
4
20
0
Order By: Relevance
“…This result is similar to a winner effect that winning small animals in previous fights tend to win against large animals in the subsequent fights (Momohara et al, 2013). A decrease in cAMP level in the brain mediated by serotonin induces the winner effect (Momohara et al, 2015(Momohara et al, , 2016. At the moment, the neurochemical and physiological bases underlying the residence effect are unclear, but certain biogenic amines like serotonin could underlie this effect.…”
Section: Evidence Of Residence Effectsupporting
confidence: 60%
See 1 more Smart Citation
“…This result is similar to a winner effect that winning small animals in previous fights tend to win against large animals in the subsequent fights (Momohara et al, 2013). A decrease in cAMP level in the brain mediated by serotonin induces the winner effect (Momohara et al, 2015(Momohara et al, , 2016. At the moment, the neurochemical and physiological bases underlying the residence effect are unclear, but certain biogenic amines like serotonin could underlie this effect.…”
Section: Evidence Of Residence Effectsupporting
confidence: 60%
“…Marmorkrebs are thought to be a parthenogenetic form of Procambarus fallax (Scholtz et al, 2003;Martin et al, 2007) and/or Procambarus virginalis (Vogt et al, 2015). They produce genetically uniform clones and their central nervous system is probably similar to that of Procambarus clarkii (Faulkes, 2016), in which agonistic interactions and winner/loser effects have been well studied (Fujimoto et al, 2011;Sato and Nagayama, 2012;Momohara et al, 2016Momohara et al, , 2018Araki et al, 2013). Their behavioural plasticity and its neurochemical basis are well characterized (Kasuya and Nagayama, 2016;Shiratori et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…They also affect neural activity underlying learning and memory (Hammer & Menzel, ; Kandel, ; Schwaerzel et al ., ; Araki et al ., ; Menses & Liy‐Salmeron, ). Previous research has also characterized the effects of biogenic amines downstream of their signalling pathways (Araki et al ., ; Araki & Nagayama, ; Kandel, ; Nagayama & Araki, ; Momohara et al ., ). Serotonin and dopamine contribute to thermotaxic memory behaviour in C. elegans (Li et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Winner and loser effects were originally defined by changes in aggression after agonistic interactions, and thus most previous research focused on the roles of androgenic hormones and associated receptors in mediating these effects. However, recent studies in invertebrates have revealed that learning and memory may also change in predictable ways with winning and losing experience (21,31,32). For instance, fruit flies (Drosophila melanogaster) can recognize conspecifics, and losers behave differently when encountering familiar versus unfamiliar opponents, suggesting that learning and memory accompany changes in social status (31).…”
Section: Discussionmentioning
confidence: 99%